Evaluating Coaches’ Program Delivery in Golf Canada’s Learn to Play Program - Kramers, Sara (Université d'Ottawa / University of Ottawa, 2018)
The purpose of this Master’s thesis was to evaluate coaches’ program delivery in Golf Canada’s national youth programming, Learn to Play, regarding two components: (a) the consistency of teaching life skills and (b) the quality of program delivery. The Learn to Play program has recently been updated to include an explicit approach to teaching life skills through golf. Data collection included a pre-season interview, three in-season observations, a post-season questionnaire, and a post-season interview. Two articles were written. Using the implicit/explicit continuum of life skills development and transfer (Bean, Kramers, Forneris, & Camiré, 2018), Article One qualitatively explored coaches’ (N = 13; Mage = 38) consistency of life skills delivery across the season. The findings revealed five profiles, with coaches categorized as being either inconsistent (i.e., progressive, overenthusiastic, unaware) or consistent (i.e., non-intentional, intentional) in their approach to teaching life skills. Using the Program Quality Assessment in Youth Sport observational measure (Bean, Kramers, Camiré, Fraser-Thomas, & Forneris, 2018), Article Two quantitatively examined program quality with two groups of coaches (N = 14; Mage = 40) for two purposes: (a) to examine whether implementation of the original (n = 5) versus the updated (n = 9) program led to differences in program quality and (b) to assess whether there was consistency or discrepancy between researcher observation scores and coach self-report scores of program quality. The findings revealed that coaches using the updated program delivered higher quality programming than coaches using the original program. Coaches also reported higher program quality scores than the researchers observed, identifying discrepancies between coach self-perceptions and researcher observations. Collectively, the findings from this Master’s thesis are a novel contribution to the literature by providing a nuanced exploration into the teaching of life skills and quality of delivery of Golf Canada’s Learn to Play programming.
Keywords: Life Skills; Positive Youth Development; Program Quality; Youth Sport; Coaching